Surgical Management Of Chronic Recurrent Genital Prolapse By Pervaginum Ovario-Hysterectomy In Six Cows - Desai, B. D.; Tank, P. H.; Vadaliya , J.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Six cows suffering from chronic recurrent genital prolapse in which the prolapse mass was infected, oedematous, lacerated and necrotic. Also the organ became swollen, hardened and friable making replacement more difficult. These types of pathological changes not responding medical management so that it requires surgical manipulation by pervaginum ovario-hysterectomy as salvage measure. To alleviate the suffering and stress, the cows were subjected to ovario-hysterectomy including resection of affected cervico-vaginal prolapsed mass through vaginal approach under mild xylazine sedation and epidural anaesthesia in lateral recumbency. Urination was facilitated by catheterization of urethra. Evaluation of surgical site were recorded for any post operative complications and if any infectious vaginal discharge were observed vaginal douching given with Povidone iodine. The complications like anorexia and weakness were observed in 4 cases. Two cows died after few days of the surgery. Four cases having uneventful recovery.